Letter to Jane Tolmach from R.E. - R.E.:::::: (1968)
A letter from R.E. to Jane Tolmach that congratulates Jane on her recent electoral victory, noting how close the race was and expressing relief and happiness at the outcome. She mentions that Jane's picture with McCarthy appeared on the front page of the Chronicle. Fowle expresses enthusiasm about continuing their work together and encourages them to stay in close contact.